Tingkat Pengetahuan Orang Tua terhadap Penyakit Pneumonia dan Imunisasi Pneumococcal Conjugate Vaccine (PCV) di Indonesia - Erlika Saputri; Dwi Endarti; Tri Murti Andayani (Faculty of Pharmacy, Universitas Gadjah Mada)
PCV immunization has been proven to be effective in preventing pneumonia, but the immunization coverage is still low in Indonesia. Good parental knowledge about pneumonia and PCV vaccine is an important factor that can support the coverage of PCV immunization. The purpose of this study was to determine the level of parental knowledge about pneumonia and PCV immunization and to know the factors that influence it. This study obeservasional design with a multi-center cross-sectional approach. Data was collected using survey to parents in 5 Provinces in Indonesia which were Provinces of DIY, Lampung, Sulawesi Tengah, Kalimantan Tengah, and Jawa Barat using convenience sampling. Study instrument consisted of questionnaire to determine sociodemographic characteristics and level of knowledge. Data was analyzed and presented descriptively and statistically using the Mann Whitney test. The results showed of 500 respondents had mean score of knowledge 80.6% ± 12.8% and median of knowledge 84.6%. Low knowledge was observed in the item of PCV immunization was not yet included in national program of immunization in Indonesia with percentage of respondents’ correct answer was 24.6%. There was significant difference in the score of knowledge about pneumonia and PCV immunization within different groups in the respondents’ characteristics of expenditure per month (p=0.001), number of responsibilities (p=0.007), experience of hearing illness (p=0,000), experience of illness (p=0.046), experience of hearing vaccines (p=0,000), and vaccine information sources (p=0.024). This study suggests the need of regular education programs for community in Indonesia to improve knowledge regarding pneumonia and PCV immunization.